测量人端粒精准长度的单分子力学方法 (2024)
本发明涉及一种测量人端粒精准长度的单分子力学方法。首先，提取目标细胞的基因组DNA；使用组合酶切，消化基因组，保留端粒DNA；分别采用地高辛和生物素对端粒DNA两端进行亲和标记，从而获得可用于单分子力学测量的端粒DNA结构。其次，将端粒结构固定于链霉亲和素包被的磁珠和抗地高辛抗体铺敷的玻璃表面之间，在单分子仪器上进行DNA力学拉伸实验。最后，使用蠕虫模型，对实测端粒长度进行纳米与碱基对之间的长度转换，即可实现端粒长度的精准测量。本发明属于精密仪器测量分析与细胞分子生物学领域，为细胞研究、健康筛查和临床药物疗效评估开发了一种直接测量端粒精准长度的新方法。 The invention relates to a monomolecular mechanics method for measuring the accurate length of human telomere. The method comprises the following steps of: firstly, extracting genome DNA of a target cell; digesting the genome by using combined enzyme digestion, and reserving telomere DNA; carrying out affinity labeling on the two ends of telomere DNA by adopting digoxin and biotin respectively soas to obtain a telomere DNA structure capable of being used for Monomolecular mechanical measurement; secondly, fixing the telomere structure between streptavidin-coated magnetic beads and the glass surface paved with the anti-digoxin antibody, and carrying out a DNA mechanical tensile experiment on a monomolecular instrument; and finally, usi